Reciprocating compressor lubrication – lubricant dilution with natural gas species and the impact on lubrication rates at various operating conditions - Schulthess, Jesse Jamison, author; Windom, Bret, advisor; Olsen, Dan, committee member; Watson, Ted, committee member (Colorado State University. Libraries, 2021)
Reciprocating compressors are ubiquitous in the natural gas industry as they provide much of the pressure necessary to move natural gas from the wellhead to the customer. Many of these compressors use lubricants to reduce friction and wear at the piston-cylinder interface. These lubricants have a difficult job for many reasons, but one phenomenon is often overlooked: gas solubility. Natural gas is soluble in the lubricant at high pressures and mixes with, or dilutes, the lubricant. Recent research has demonstrated that this dilution may reduce a lubricant's viscosity so far that the lubricant cannot adequately protect the compressor. However, questions remain. First, how quickly do a gas and lubricant mix? Second, are results from previous studies applicable to the field? Third, how much lubricant is required for proper compressor lubrication? To address the first question, an experiment was devised to measure the dilution of a lubricant while it mixed with natural gas. This "dilution rate" was measured for multiple lubricants subjected to a range of temperatures and pressures. These experiments indicated that lubricants quickly obtain equilibrium with the gas stream which implies that the equilibrium viscosity of the gas-lubricant mixture is an accurate estimate of the lubricant's viscosity inside an operating compressor. To answer the second question, samples of used lubricant were collected from the field at various operating conditions. These samples were subsequently depressurized in an enclosed chamber allowing for an analysis of the gas dissolved in the lubricant. Results showed that the lubricant absorbed higher proportions of heavier hydrocarbons (C2+) than methane even when the natural gas stream was mostly methane. To answer the third question, a model of the piston-cylinder interface was created to estimate the lubricant film thickness in a reciprocating compressor. Many prior researchers have measured or estimated the lubricant film thickness for internal combustion engines but the piston ring geometry in a reciprocating compressor is drastically different. Suggestions for lubricants and lubrication rates are made using this model and compared with current industry experience.